Misperceived Luminance Gradients in an Hourglass Illusion. (August 2019) - Anstis, Stuart
A square contains a linear luminance gradient from white at the top to black at the bottom. Pinching this in at the waist forms an hourglass figure of two tip-to-tip triangles. The pinch reduces the perceptual gradient within each triangle, making the pale upper triangle and the dark lower triangle both look more uniform in brightness We attribute this to undersampling of the mid-greys.